Potential of low-density genotype imputation for cost-efficient genomic selection for resistance to Flavobacterium columnare in rainbow trout (Oncorhynchus mykiss) - Fraslin, Clémence; Robledo, Diego; Kause, Antti; Houston, Ross D. (Springer Science and Business Media LLC, 2023)
Background Flavobacterium columnare is the pathogen agent of columnaris disease, a major emerging disease that afects rainbow trout aquaculture. Selective breeding using genomic selection has potential to achieve cumulative improvement of the host resistance. However, genomic selection is expensive partly because of the cost of genotyping large numbers of animals using high-density single nucleotide polymorphism (SNP) arrays. The objective of this study was to assess the efciency of genomic selection for resistance to F. columnare using in silico low-density (LD) panels combined with imputation. After a natural outbreak of columnaris disease, 2874 challenged fsh and 469 fsh from the parental generation (n=81 parents) were genotyped with 27,907 SNPs. The efciency of genomic prediction using LD panels was assessed for 10 panels of diferent densities, which were created in silico using two sampling methods, random and equally spaced. All LD panels were also imputed to the full 28K HD panel using the parental generation as the reference population, and genomic predictions were re-evaluated. The potential of prioritizing SNPs that are associated with resistance to F. columnare was also tested for the six lower-density panels. Results The accuracies of both imputation and genomic predictions were similar with random and equally-spaced sampling of SNPs. Using LD panels of at least 3000 SNPs or lower-density panels (as low as 300 SNPs) combined with imputation resulted in accuracies that were comparable to those of the 28K HD panel and were 11% higher than the pedigree-based predictions. Conclusions Compared to using the commercial HD panel, LD panels combined with imputation may provide a more afordable approach to genomic prediction of breeding values, which supports a more widespread adoption of genomic selection in aquaculture breeding programmes
Keywords: genomic selection; animal breeding; aquaculture; rainbow trout; disease resistance